The forecast of sales in the company, what role to improve performance? - كروشة, اكرام (جامعة مسيلة, 2018)
Nowadays, performance is becoming one of the top concerns of companies and the real driver of their success; it is seen as the achievement of the objectives of the company and the contribution to the improvement of its value. It therefore becomes necessary to have the control of the knowledge act by the assembly of the tools of control of management, the sales forecasting system is one of those tools that allows the company to adapt to this environment characterized by uncertainty and complexity. The purpose of this study is to investigate whether sales forecasting can really contribute to improving company’s performance, so to meet the objectives of the study, we will try to clarify the modern vision of the performance that represents a fundamental condition for the continuity of the company ,as well as the need to set up a performance management system, with the various tools that the company can acquire, while emphasizing the measure of this performance which represents a complex and indispensable task at the same time , after we will clarify who are the beneficiaries of the company's performance and the links that unite them. Then, it will be proposed to study the different methods of forecasting sales with a scientific approach, some clarifications of this concept will be proposed to confirm his importance within companies, as well as the steps of developing this forecasts. In that case we will expose the methods of forecasting sales, qualitative methods such as Delphi methods, purchase intention surveys, and statistical and econometric (quantitative) methods that we will use in our empirical study, namely, chronological series. The empirical aspect will be based on a modeling test using the econometric model of sales forecasts in an Algerian dairy named El Amir Tizi, specialized in the production of milk and dairy products, this practical study will begin with the determination of the variables of the study (dependent and independent), through the technique of collection and validation of the data of the company and finally the analysis of the results obtained. The main results of this study show that the improvement in the performance of the company is dependent on a good sales forecast; it represents an important tool for decision-making, with the minimization of the level of uncertainty and the coverage of environmental risks. Sales forecasting not only allows companies a better periodicity of information, but also it can be considered as an instrument of communication, an essential element of any company’s information system.
Keywords: sales forecasting; performance; modeling; management control.